Surviving ectopic Cushing's syndrome: quality of life, cardiovascular and metabolic outcomes in comparison to Cushing's disease during long-term follow-up. Issue 2 (August 2018) - Osswald, Andrea; Deutschbein, Timo; Berr, Christina M; Plomer, Eva; Mickisch, Anne; Ritzel, Katrin; Schopohl, Jochen; Beuschlein, Felix; Fassnacht, Martin; Hahner, Stefanie; Reincke, Martin
Abstract : Objective: Aim of our study was to analyze long-term outcome of patients with the ectopic Cushing's syndrome (ECS) compared to patients with Cushing's disease (CD) regarding cardiovascular, metabolic, musculoskeletal and psychiatric comorbidities. Design: Cross-sectional study in patients with ECS and CD in two German academic tertiary care centers. Methods: Standardized clinical follow-up examination was performed including health-related quality of life (QoL) in 21 ECS patients in long-term remission (≥18 months since successful surgery). Fifty-nine patients with CD in remission served as controls. Results: Time from first symptoms to diagnosis of Cushing's syndrome (CS) was shorter in ECS than in CD (8.5 (IQR: 30.3) vs 25 (IQR: 39.0) months, P  = 0.050). ECS patients had lower self-reported psychiatric morbidity compared to CD (19% vs 43%, P  = 0.050) at follow-up. Moreover, female ECS patients reported favorable scores for QoL in the SF-36 questionnaire (mental health: 92 (IQR: 30) vs 64 (IQR: 32) in CD, P  = 0.010) and a Cushing-specific QoL questionnaire (73 (IQR: 18) vs 59 (IQR: 36) in CD, P  = 0.030). In a pooled analysis of ECS and CD patients, QoL correlated with time from first symptoms until diagnosis of CS, but not with urinary free cortisol levels or serum cortisol after dexamethasone at the time of diagnosis. Long-term outcomes regarding hypertension, metabolic parameters, bone mineral density and grip strength were comparable in ECS and CD. Conclusions: Our data support the concept that time of exposure to glucocorticoid excess appears to be a better predictor than peak serum cortisol levels at the time of diagnosis regarding long-term psychiatric morbidity and QoL.